(untitled) (Comprehensive Journal of Science, 2026)
Background: Oral tumors, including oral squamous cell carcinoma (OSCC) and verrucous carcinoma (VC), represent a significant public health concern due to their high morbidity and mortality rates. Public knowledge and perceptions regarding these tumors play a crucial role in early detection, treatment adherence, and overall prognosis. Objective: This study aimed to assess patient knowledge, perceptions, and treatment beliefs regarding oral tumors, and to identify factors predicting perceived treatability among patients attending specialized health centers in Libya. Methods: A descriptive cross-sectional design was employed. The study population included 50 patients (13 males, 37 females) attending the National Cancer Institute in Sabratha, Al-Afrah Center in Al-Ajilat, and Hamda Al-Qarawi Clinic. Data were collected using a structured questionnaire comprising 10 items, validated by a panel of dental specialists. Descriptive statistics summarized demographic characteristics, knowledge, and perceptions, while inferential analyses, including Chi-square tests and binary logistic regression, evaluated associations and predictors of perceived treatability. Statistical significance was set at p < 0.05. Results: The majority of participants were female (60%). Only 16% recognized oral tumors as serious, and 20% believed complete blood count could detect tumors. Misconceptions regarding infectivity were common: 36% considered oral tumors infectious, and 30% believed they could be transmitted orally. Belief in the effectiveness of antibiotics significantly predicted perceived treatability (OR = 3.00; 95% CI: 1.20–7.50; p = 0.02). No significant associations were found between gender and knowledge or perceptions. Weak non-significant relationships were observed between diagnostic methods (CBC, X-ray) and perceived treatability. Conclusion: The study revealed significant gaps in patient knowledge and misconceptions regarding oral tumors, particularly concerning severity, transmissibility, and treatment. Belief in antibiotic efficacy strongly influenced perceived treatability, underscoring the need for targeted educational interventions. Findings support the implementation of integrated clinical and public health strategies to improve awareness, early detection, and appropriate management of oral tumors in Libya.